Optimasi Pengaturan Pembangkit Hidro Kaskade Sungai Brantas untuk Meningkatkan Cascade Effectiveness - Mochammad Syaiful Bakri; Margianto; Nur Robbi; Mochammad Basjir (Jurnal Serambi Engineering, 2024)
Hydropower with a cascade scheme utilises the energy potential of water in a sustainable manner. The Brantas River area is used to generate 4 (four) hydropower plants (HEPP) that are arranged in series from upstream to downstream, namely Sengguruh HEPP, Sutami HEPP, Wlingi HEPP and Lodoyo HEPP. From December 2022 to November 2023, the four hydropower plants can produce 888,629,472 kWh of electricity. However, there is still potential for electricity generation that can be optimised from the unused water potential (spillwaywater) of 553.61 million m3. The optimisation management system provides a solution for utilising water energy sources by formulating a mathematical model using Solver in the Microsoft Excel application to plan the water level of the Sutami reservoir, hydropower load settings and peak/off-peak times at each hydropower plant. By implementing an optimisation, electrical energy production has the potential to reach 951,796,287 kWh or an increase of 7.11% in the period December 2022 to November 2023 by minimising the occurrence of spillway water by up to 92.40% or 551.61 million m3. As a result, the cascade efficiency of the hydropower plants of the Brantas River cascade was increased by 2.87% or 0.003 kWh/m3.